A 3-V fully differential distributed limiting driver for 40-Gb - McPherson, D.S.
A fully differential 40-Gb/s electro-absorption modulator driver is presented. Based on a distributed limiting architecture, the circuit can supply up to 3.0-Vpp (peak-to-peak) per side in a 50-Ω load at data rates as high as 44 Gb/s. Both the input and the output are internally matched to 50 Ω and exhibit return loss of better than 10 dB up to 50 GHz. Additional features of the driver include the use of a single -5.2-V supply, output swing control (1.7-3.0-Vpp per side), dc output offset control (-0.15 V to -1.1 V), and pulsewidth control (30% to 66%). The driver architecture was optimized based on a comprehensive analytical derivation of the frequency response of cascaded source-coupled field-effect transistor logic blocks using both single and double source-follower topologies.
Keywords: 10 dB; 3 V; 40 Gbit/s.; 50 GHz; 50 ohm; Electro-absorption modulator; Fully-differential distributed limiting driver; Optical transmission system; Source-coupled FET logic